Implications of the International Paediatric Multiple Sclerosis Study Group consensus criteria for paediatric acute disseminated encephalomyelitis: a nationwide validation study. (10th May 2018) - Boesen, Magnus S; Blinkenberg, Morten; Koch‐Henriksen, Nils; Thygesen, Lau C; Uldall, Peter V; Magyari, Melinda; Born, Alfred P
Abstract : Aim: The International Paediatric Multiple Sclerosis Study Group (IPMSSG) has proposed criteria for acute disseminated encephalomyelitis (ADEM) not evaluated in clinical practice. Our objective was to assess epidemiological implications of the IPMSSG criteria for ADEM in a cohort study using prospectively collected data. Method: We identified all diagnosed cases of ADEM in Denmark between 2008 and 2015 from the Danish National Patient Register by International Classification of Diseases 10 codes assigned to acute demyelinating episodes, and we reviewed all medical records to validate ADEM. Results: We found 52 children up to the age of 18 years with a verified clinical diagnosis of ADEM (incidence rate 0.54/100 000 person‐years; all had abnormal brain magnetic resonance imaging). Only 18 (35%) fulfilled the IPMSSG criteria regarding encephalopathy and polyfocal neurological deficits. Among all 52 children with ADEM, 33 per cent had clinical sequelae after a median follow‐up of 4 years 6 months (range: 10mo–8y 3mo). Surprisingly, none progressed to multiphasic ADEM or multiple sclerosis, but median age at end of follow‐up was only 10 years 9 months (range: 2y–24y 3mo). Interpretation: Among 52 children with ADEM, none converted to multiphasic ADEM or multiple sclerosis (median follow‐up: 4y 6mo; range: 10mo–8y 3mo). Applying the IPMSSG criteria to all children with a diagnosis of ADEM leaves 65 per cent of the cases without a diagnosis and lowers the incidence rate of paediatric ADEM. What this paper adds: The incidence of paediatric acute disseminated encephalomyelitis (ADEM) was 0.54 per 100 000 person‐years in children younger than 18 years. Only 35 per cent of children with ADEM fulfilled the International Paediatric Study Group consensus criteria. ADEM in clinical practice was primarily based on magnetic resonance imaging findings. Paediatric neurologists diagnosed ADEM in the absence of encephalopathy. None of the children with ADEM progressed to multiple sclerosis/multiphasic ADEM during follow‐up. What this paper adds: The incidence of paediatric acute disseminated encephalomyelitis (ADEM) was 0.54 per 100 000 person‐years in children younger than 18 years. Only 35 per cent of children with ADEM fulfilled the International Paediatric Study Group consensus criteria. ADEM in clinical practice was primarily based on magnetic resonance imaging findings. Paediatric neurologists diagnosed ADEM in the absence of encephalopathy. None of the children with ADEM progressed to multiple sclerosis/multiphasic ADEM during follow‐up. This article is commented on by Hardy on page1070 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.